Penekanan Interaksi dalam Komunikasi Sepanjang Pembelajaran di Hospital (Sains Humanika, 2015)
This study aims to identify the level of trainee doctors communication competence, the effect of Kolb's learning theory applications to trainee doctors communication competence. In addition, the researchers also identify the phase in Kolb's learning theory is the most dominant impact on trainee doctors communication competence during housemanship. Respondents of this research were 102 trainee doctors at a hospital in Johor Bahru. Data were collected using a survey questionnaire has three parts, A, B, and C. Each section includes demographic factors, phases of learning and competence. This study uses trainee doctor communication competence as the dependent variable and the theory of Kolb's learning phase as the dependent variable. The collected data was then analyzed using descriptive statistics (mean, frequency, percentage) and inferential statistics (pearson correlation and multiple regression). The findings showed that the level of communication competency is moderate. Next, the analysis of the correlation test showed all phases of learning has a positive relationship with competence. Meanwhile multiple regression test showed conceptual phase has the highest Î² value and this proves that the phase of the highest contribution to competency of trainee doctors during housemanship.Â
Keywords: Communication competence; trainee doctors; housemanship; Kolb learning theory; learning phase